Development Of Case Based Learning Rps And Student Responses To Learning Outcomes In The Physics Education Program - Desy Ayunda; Wulanda; Ade Widya Pratiwi; Fatquraini (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The integration of science and religion presents a challenge in higher education, particularly in courses that link scientific knowledge with the teachings of the Qur'an. The Case Based Learning (CBL) approach is considered effective in enhancing students' understanding and engagement through the analysis of real-life cases. This study aims to develop a Semester Learning Plan (RPS) based on CBL for the course Science in the Qur'an using the 4D development model (Define, Design, Development, Disseminate). The Define phase includes identifying issues, setting learning objectives, and planning the necessary resources. The Development phase focuses on the creation and validation of the RPS, which is reviewed by content and language experts. Subsequently, trials were conducted with small and large groups to assess the practicality and effectiveness of the RPS. The results indicate that the CBL-based RPS is highly practical, with practicality scores of 90.62% for the small group and 92.96% for the large group. Additionally, the RPS proved effective in improving students' learning outcomes, with significant improvements in understanding and analytical skills. This study shows that the CBL-based RPS can enrich learning by integrating science and religious teachings, making a positive contribution to education in the fields of physics and Islamic studies.